ℵ1-directed inverse systems of continuous images of arcs. (15th July 2000) - Lončar, Ivan
Abstract : The main purpose of this paper is to prove that ifX = { X a, p a b, A } is a usualℵ 1 -directed inverse system of continuous images of arcs with monotone bonding mappings, thenX = lim X is a continuous image of an arc (Theorem 2.4). Some applications of this statement are also given.